2002
DOI: 10.1108/eb026976
|View full text |Cite
|
Sign up to set email alerts
|

The Valuation of European Financial Firms

Abstract: We extend the recent literature concerning accounting based valuation models to investigate financial firms from six European countries with substantial financial sectors: France, Germany, Italy, Netherlands, Switzerland and the UK. Not only are these crucial industries worthy of study in their own right, but unusual accounting practices, and inter‐country differences in those accounting practices, provide valuable insights into the accounting‐value relationship. Our sample consists of 7,714 financial firm/yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The sample excludes financial firms, property companies and investment trusts. This restriction is conventional as the relationship between value and accounting numbers is thought to be very different for financial and industrial firms, although Danbolt and Rees (2001) show that for certain classes of financial companies this is not the case. Firms with double‐class securities (e.g.…”
Section: Data and Empirical Model Specificationmentioning
confidence: 99%
“…The sample excludes financial firms, property companies and investment trusts. This restriction is conventional as the relationship between value and accounting numbers is thought to be very different for financial and industrial firms, although Danbolt and Rees (2001) show that for certain classes of financial companies this is not the case. Firms with double‐class securities (e.g.…”
Section: Data and Empirical Model Specificationmentioning
confidence: 99%
“…The accuracy of valuations based on actual EPS in Canada, Germany, and Japan was very low, while the performance of valuations based on earnings in France was quite accurate. The findings of Danbolt and Rees (2002) in six European countries (France, Germany, Italy, the Netherlands, Switzerland and the United Kingdom) revealed that the book-value accounting model worked relatively well for companies in the financial sector, while valuations based on large profits were more relevant in countries such as the Netherlands, the United Kingdom, and Italy than the other three countries in their sample. This finding is also supported by Schantl (2016) and Yin et al (2016).…”
Section: Introductionmentioning
confidence: 97%
“…Our main references for the present work are Cheng [2005], and Bowen et al [2002]. Danbolt and Rees [2002] extend the recent literature concerning accounting based valuation models to investigate financial firms from six European countries with substantial financial sectors: France, Germany, Italy, Netherlands, Switzerland and the UK. In most countries they find that the valuation models work as well, or better, in explaining cross-sectional variations in the market-to-book ratio for financial firms as they do for industrial and commercial firms in the same countries, although Switzerland is an exception to this generalization.…”
Section: Determinants Of Abnormal Profitabilitymentioning
confidence: 99%